Factors Influencing Outcomes of Children Hospitalized with Acute Severe Malnutrition - Viramitha Kusnandi Rusmil; Siska Wiramihardja; Adhitya AP; Dida A Gurnida (Althea Medical Journal, 2018)
Background: Nutrition is still a global health issue, and improving nutrition is among the targets of the Sustainable Developmental Goals (SDGs). One of Indonesia’s SDGs indicators is to reduce prevalence of malnutrition in children. Indonesia, as a developing country, implements a comprehensive malnutrition treatment program for children, including various aspects related to management of children with acute malnutrition. The purpose of this study was to identify factors associated with the outcome of children hospitalized with acute severe malnutrition. Methods: This cross sectional study enrolled 195 children with severe acute malnutrition, admitted to hospital from November 2016 to August 2017. Statistical Analysis was conducted using multivariable logistic regression to identify factors associated with the outcome. Adjusted Ratio with Confident Interval 95% and the value of P <0 .05 was considered significant. Result: A total of 195 children were diagnosed havings acute severe malnutrition. A history of complete immunization status (p value <0.001) was proved to be directly proportional to the recovery rate of patients with acute severe malnutrition. Provision of other types of antibiotic (p value 0.001) showed to increase recovery rates of patients with acute severe malnutrition. Several comorbid diseases reduced recovery rates such as pneumonia (Crude OR 0.619) tuberculosis (Crude OR 0.606) and HIV (p value 0.08).Conclusions: This study shows that although the provided treatments are appropriate with the standard treatment for severe malnutrition, they still encounter high levels of morbidity. Further large-scale studies should be conducted to develop better interventions and management of acute severe malnutrition, in order to achieve better outcome.